Reaction of in situ electrogenerated superoxide ion (O2-·) with some compounds having labile hydrogens - Singh K.N.; Singh S. (My University, 2025)
The reaction of various substrates viz., 2-benzylpyridine (1a), 2,2′- methylene-bis-(5-acetylthiophene) (1b), 1-benzyl-4-hydroxypiperidine (1c), fluorene (1d), 2-nitrofluorene (1e), anthrone (1f), 9,10-dihydroanthracene (1g), xanthene (1h), 9-hydroxyxanthene (1i), 9-phenylfluorene (1j) and 9-phenylxanthene (1k) has been studied with superoxide ion (in situ electrogenerated) in N,N- dimethylformamide (DMF) using controlled potential macroelectrolysis. The above components are oxidatively transformed into ketones or alcohols as the only isolable products. A plausible mechanism via hydrogen abstraction is also hypothetized.